A Management System Exempt from Power Learning to Manage with Consideration for Others - Bourion, C. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
The author argues that power in organizations has negative and counter-productive effects: management should be based on self-guidance and maximizing each individual's creative resources. Arguing that mangers should focus on developing efficiency, empathy and imagination, this includes questionnaires so readers can assess their management approach.